PREPARATION OF PARENTING PROGRAMS FOR PAUD MANAGEMENT AND EDUCATION IN TK SARTIKA VILLAGE BINA JAYA KECAMATAN TOLANGOHULA GORONTALO - YANTI NGADI; RUSLIN W. BADU; MISRAN RAHMAN (International Journal of Innovations in Engineering Research and Technology, 2021)
Advances in science and technology are getting higher but problems are increasing, and challenges are increasing. Likewise, formal, non-formal and informal education always has a weak spot on each line. This condition requires educators and educational institutions to think harder so they do not go hand in hand with the times. Cooperation between institutions and the education environment is very much needed so that there will be no regrets later and children's education can be developed optimally. One way that can be done in early childhood education is to create a mature cooperation program and this program must be well designed.